2020
DOI: 10.4155/tde-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Punctum and Canalicular Anatomy for hydrogel-based Intracanalicular Insert Technology

Abstract: Aim: Despite advances in cataract surgery, postoperative ocular inflammation and pain occurs. To address compliance issues with topical corticosteroid administration, a hydrogel-based dexamethasone insert was developed for intracanalicular administration. The objective is to understand the anatomy to best administer the insert and learn how the anatomy and hydrogel properties help retain the insert in the canaliculus over time. Materials & methods: Human cadavers (n = 5) were dissected to assess dimensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…After the drug is eluted over 30 days, the hydrogel insert begins to slowly hydrolyze, eventually liquefying, then clearing the nasolacrimal system by flushing through the nasolacrimal duct. 18 In the rare case where removal of the insert is needed, manual expression or saline irrigation can be administered. 17
Figure 1 Placement of the Dexamethasone Intracanalicular Insert in the canaliculus of the eye.
…”
Section: Methodsmentioning
confidence: 99%
“…After the drug is eluted over 30 days, the hydrogel insert begins to slowly hydrolyze, eventually liquefying, then clearing the nasolacrimal system by flushing through the nasolacrimal duct. 18 In the rare case where removal of the insert is needed, manual expression or saline irrigation can be administered. 17
Figure 1 Placement of the Dexamethasone Intracanalicular Insert in the canaliculus of the eye.
…”
Section: Methodsmentioning
confidence: 99%
“…15 The dexamethasone hydrogel insert is fluorescein-conjugated to aid with visualization. 16 Large placebo-controlled studies have demonstrated the efficacy of the insert for alleviating inflammation and pain following cataract surgery 17,18 leading to FDA approval for the treatment of ocular inflammation and pain following ophthalmic surgery. 19 Patients treated with the dexamethasone insert reported favorably on overall satisfaction, convenience and comfort.…”
Section: Introductionmentioning
confidence: 99%